Increasing Number of Individuals Receiving Hepatitis B nucleos(t)ide Analogs Therapy in Germany, 2008–2019 - Maisa, Anna; Kollan, Christian; an der Heiden, Matthias; van Bömmel, Florian; Cornberg, Markus; Mauss, Stefan; Wedemeyer, Heiner; Schmidt, Daniel; Dudareva, Sandra (Frontiers in Public Health, 2021)
Background: Germany is a low prevalence country for hepatitis B virus (HBV) infection with higher prevalence in vulnerable groups. The number of treated chronic hepatitis B (CHB) patients is unknown. We aimed to determine the number of CHB patients treated with nucleos(t)ide analogs (NUCs), the treatment costs within the statutory health insurance (SHI) in Germany and per patient per month. Methods: Data on pharmacy bills of NUCs to patients with SHI between 2008 and 2019 were purchased from Insight Health™ and described. Negative binomial regression was used for trend analysis. Results: Number of patients increased between 2008 and 2019 (4.9% per year) with little changes in treatment options. Overall prescription costs were increasing (6.7% per year on average) until the introduction of tenofovir and entecavir generics in 2017 after which costs decreased by 31% in 2019. Average therapy costs peaked at 498 Euro per patient per month in 2016 and decreased to 214 Euro in 2019. Prescriptions changed from 30 to 90 pills per pack over time. HBV therapy was prescribed to 97% by three medical specialist groups, mainly specialists in internal medicine (63%), followed by hospital-based outpatient clinics (20%) and general practitioners (15%). Contrary to guideline recommendation, adefovir was still prescribed after 2011 for 1–5% of patients albeit with decreasing tendency. Prescriptions per 100,000 inhabitants were highest in Berlin and Hamburg. Conclusion: Our data shows, that the number of treated CHB patients increased steadily, while NUC therapy costs decreased. We recommend continued testing and treatment for those eligible to prevent advanced liver disease and possibly decrease further transmission of HBV.